PENGARUH GROWTH OPPORTUNITY , INTELLECTUAL CAPITAL, ROA DAN LEVERAGE PADA FIRM VALUE - Irma Indira (STIE Mahardhika, 2022)
This study aims to test and analyze empirically the effect of Growth Opportunity, Intellectual Capital, ROA and leverage on Firm Value. This research was conducted by making observations in manufacturing companies on the Indonesia Stock Exchange. The sampling technique used was purposive sampling. In this study, hypothesis testing uses PLS (Partial Least Square) application tools 3.3. The results of this study indicate that if Growth Opportunity, ROA and Leverage affect the firm value while the firm value cannot be influenced by the Intellectual Capital variable.